The fractured dark - O'Keefe, Megan E., 1985- (The Devoured Worlds, 2023)
"Naira and Tarquin have escaped the pull of a dying planet, and are now bound together to find the truth behind the all-powerful Mercator family and the blight that has been killing habitable planets. But the Mercator secrets are buried deep, and Tarquin's father, the head of Mercator, knows the revolutionaries are on his tail. When Tarquin's father disappears, taking the rest of his family and the universe's remaining supply of starship fuel with him, chaos breaks loose between the universe's ruling families. And Naira's revolution must be put aside for the sake of humanity's immediate survival"--